Nurturing Nationalism Character Values at the Primary Schools in Jayapura, Papua - Abu Bakar, Kosasih Ali; Noor, Idris HM; Widodo, Widodo (Cakrawala Pendidikan, 2018)
Abstract: Several surveys conducted by non-governmental organizations indicated the decline of nationalism sense in Indonesia and a real threat of separatist movements insisting to separate from Indonesia. To anticipate it, schools as the guard of education need to be the agents of nationalism through the learning process. This study aims to explore the information, activities and constraints faced by schools in nurturing nationalism character values at school as well as to formulate the problem solving model. This study employed qualitative descriptive approach. The sample of the study was taken from some rural and urban schools in Jayapura district. These schools have been appointed as the role model for character education reinforcement by the Ministry of Education and Culture of the Republic of Indonesia. Jayapura District was chosen since several studies revealed that Papua still indicated active separatist movements. This research began with a secondary data analysis about nationalism in some countries and some regions in Indonesia. Focus group discussion was subsequently conducted with some local teachers and officials to verify and validate the data. The information obtained was then analyzed step by step. The result of the study shows that schools have done possible and creative programs to nurture nationalism character values at school as well as involving their neighbourhood in the reinforcement of nationalism values.Keywords: nationalist, school, education, character PENUMBUHAN NILAI KARAKTER NASIONALIS PADA SEKOLAH DASAR DI KABUPATEN JAYAPURA PAPUA Abstrak: Dari hasil beberapa survei yang dilakukan oleh lembaga swadaya masyarakat mengindikasikan adanya penurunan rasa nasionalisme di Indonesia dan masih nyata adanya ancaman gerakan separatis yang ingin memisahkan diri dari Indonesia. Guna mengantisipasi hal tersebut, sekolah sebagai garda terdepan pendidikan harus bisa menjadi agen penjaga nasionalisme melalui proses pembelajaran. Penelitian ini bertujuan untuk menggali informasi dan aktivitas serta kendala sekolah dalam upaya menumbuhkan nilai-nilai karakter nasionalis sekaligus memformulasikan dalam sebuah model.  Penelitian dilakukan dengan menggunakan pendekatan deskriptif kualititatif. Sampel penelitian adalah Kabupaten Jayapura yang terdiri atas beberapa sekolah yang berada di perkotaan dan perdesaan yang telah menjadi role model penguatan pendidikan karakter oleh Kementerian Pendidikan dan Kebudayaan. Kabupaten Jayapura terpilih karena berdasarkan hasil dari beberapa penelitian Papua masih terindikasi sebagai daerah yang masih cukup aktif gerakan separatisnya. Penelitian ini diawali dengan analisis data sekunder terkait nasionalisme di beberapa negara, beberapa daerah di Indonesia yang kemudian dilanjutkan dengan diskusi kelompok terpumpun dengan guru-guru dan aparat daerah  setempat dalam rangka verifikasi dan validasi data. Informasi yang didapat kemudian dianalisis secara bertahap. Hasil penelitian ini memperlihatkan bahwa sekolah sudah berupaya semaksimal mungkin dan sekreatif mungkin dalam menumbuhkan nilai karakter nasionalis di sekolah maupun dengan mengikutsertakan lingkungan di sekitar sekolah.Kata Kunci: nasionalis, sekolah, pendidikan, karakter